Personality at Work: Understanding HEXACO Traits Behind Citizenship Behavior - Noviana, Putri Yogi; ’Alwan, Faiz Fatihul (Universitas Ahmad Dahlan, 2025)
Organizational Citizenship Behavior (OCB) plays a crucial role in organizational effectiveness; however, not all employees are willing to demonstrate such voluntary behaviors. This study aims to examine the influence of HEXACO personality dimensions on OCB among millennial employees. A quantitative approach was employed, involving 331 participants who had worked for at least one year. Measurements were conducted using validated HEXACO and OCB scales, and the data were analyzed using multiple linear regression. The results indicate that the HEXACO model significantly predicts OCB (R² = 0.518; p < 0.001). Partially, Honesty-Humility, Extraversion, and Agreeableness have a significant positive effect on OCB, whereas Emotionality, Conscientiousness, and Openness are not significant predictors. These findings highlight that ethical character, social engagement, and cooperative tendencies represent key personality factors that promote extra-role behaviors and contribute positively to organizational performance.